Electrophysiologic characteristics of tremor in Parkinson?s disease and essential tremor - Ederson Cichaczewski; Renato P. Munhoz; Joaquim M. Maia; Percy Nohama; Edison M. Nóvak; Helio A. Teive (Arquivos de Neuro-Psiquiatria, 2014)
Tremor in essential tremor (ET) and Parkinson’s disease (PD) usually present specific electrophysiologic profiles, however amplitude and frequency may have wide variations. Objective: To present the electrophysiologic findings in PD and ET. Method: Patients were assessed at rest, with posture and action. Seventeen patients with ET and 62 with PD were included. PD cases were clustered into three groups: predominant rest tremor; tremor with similar intensity at rest, posture and during kinetic task; and predominant kinetic tremor. Results: Patients with PD presented tremors with average frequency of 5.29±1.18 Hz at rest, 5.79±1.39 Hz with posture and 6.48±1.34 Hz with the kinetic task. Tremor in ET presented with an average frequency of 5.97±1.1 Hz at rest, 6.18±1 Hz with posture and 6.53±1.2 Hz with kinetic task. Seven (41.2%) also showed rest tremor. Conclusion: The tremor analysis alone using the methodology described here, is not sufficient to differentiate tremor in ET and PD.